Soybean Yield as Affected by Planting Date and Maturity Group in the Southern Plains. Issue 1 (1st December 2013) - Barreiro, A. S.; Godsey, C. B.
Abstract : Soybean [ Glycine max (L.) Merr.] is normally planted in the Southern Plains between early April and early May using maturity groups (MG) III and IV, or from late May through June using MG IV and V. Planting date (PD) and MG can greatly impact soybean seed yield in rainfed production systems. Our objective was to determine the effects of PD and MG on yield to assist Southern Plains soybean producers in choosing the correct MG for a specific planting period. Five MGs ranging between 3.8 and 5.6 were sown at five PDs between early April and late July in Stillwater, OK in 2009 and 2010 and in Lahoma, OK in 2010. Across site‐years, soybean seed yield was reduced 215 kg ha −1 (3.2 bu ac −1 ) per week when planted after DOY (day of year) 149 (29 May). Overall, MG had little effect on yield if a MG IV or V cultivar was used. Based on these three site‐years of research, selection of soybean cultivars within MG IV to V and planting before 29 May provides the greatest chance to maximize soybean seed yield in the Southern Plains.